The development of chemical approaches to fossil hominin ecology in South Africa - Julia Lee-Thorp; Matt Sponheimer (South African Journal of Science)
When Dart recognised the fossilised skull of the Taung Child as a hominin ancestor, he also observed that its “sere environment” produced few foods preferred by African apes in equatorial forests. He thus set in motion an inquiry into the dietary and environmental proclivities of fossil hominins. His observations ultimately led him to suggest a strong reliance on meat-eating, later elaborated into a hunting model. Subsequent investigations into the diets of the South African australopithecines led to the development of new approaches including dental microwear, stable light isotopes, and trace element analyses, which together led to a new focus on the prime importance of plant foods, for which there had been little direct behavioural evidence. Here we review why and how stable and radiogenic isotope approaches to hominin diet and residence patterns were developed in South Africa, the problems that had to be addressed, and the subsequent outcomes.